Using modern human cortical bone distribution to test the systemic robusticity hypothesis. Issue 119 (June 2018) - Baab, Karen L.; Copes, Lynn E.; Ward, Devin L.; Wells, Nora; Grine, Frederick E.
Abstract: The systemic robusticity hypothesis links the thickness of cortical bone in both the cranium and limb bones. This hypothesis posits that thick cortical bone is in part a systemic response to circulating hormones, such as growth hormone and thyroid hormone, possibly related to physical activity or cold climates. Although this hypothesis has gained popular traction, only rarely has robusticity of the cranium and postcranial skeleton been considered jointly. We acquired computed tomographic scans from associated crania, femora and humeri from single individuals representing 11 populations in Africa and North America ( n  = 228). Cortical thickness in the parietal, frontal and occipital bones and cortical bone area in limb bone diaphyses were analyzed using correlation, multiple regression and general linear models to test the hypothesis. Absolute thickness values from the crania were not correlated with cortical bone area of the femur or humerus, which is at odds with the systemic robusticity hypothesis. However, measures of cortical bone scaled by total vault thickness and limb cross-sectional area were positively correlated between the cranium and postcranium. When accounting for a range of potential confounding variables, including sex, age and body mass, variation in relative postcranial cortical bone area explained ∼20% of variation in the proportion of cortical cranial bone thickness. While these findings provide limited support for the systemic robusticity hypothesis, cranial cortical thickness did not track climate or physical activity across populations. Thus, some of the variation in cranial cortical bone thickness in modern humans is attributable to systemic effects, but the driving force behind this effect remains obscure. Moreover, neither absolute nor proportional measures of cranial cortical bone thickness are positively correlated with total cranial bone thickness, complicating the extrapolation of these findings to extinct species where only cranial vault thickness has been measured.